Property Tax Responses to State Aid Cuts in the Recent Fiscal Crisis - Dye, Richard F.; Reschovsky, Andrew (My University, 2007)
The paper examines whether states increased property taxes between 2002 and 2004 in order to maintain the level of public services in light of large cuts in state intergovernmental grants resulting from state fiscal crises.